Comparing shape along growth trajectories in two marine snail ecotypes of Littorina saxatilis: a test of evolution by paedomorphosis. (29th August 2020) - Gefaell, J; Varela, N; Rolán-Alvarez, E
ABSTRACT: Two sympatric ecotypes ('crab' and 'wave') of Littorina saxatilis are adapted to different microhabitats. It has been claimed, based on the comparison of proteomic differentiation across ontogeny, that the wave ecotype may have evolved by paedomorphosis from an ancestor more similar to the crab ecotype. Here, we test the paedomorphosis hypothesis at a morphological level by comparing crab and wave specimens from two localities using the pattern of shell shape differentiation across ontogeny. The results obtained show a pattern of shell shape differentiation similar to the one observed in previous proteomic studies, but such a pattern could be caused by different modes of evolution, and not necessarily by paedomorphosis. This study emphasizes that in addition to studying the pattern of differentiation, the direction of the evolutionary change across ontogeny has to be analysed before conclusions can be drawn on particular developmental modes of evolution.